Spatial practices : modes of action and engagement with the city - Dodd, Melanie (Abingdon, Oxon ; New York, NY : Routledge, 2020)
This book explores spatial practices', a loose and expandable set of approaches that embrace the political and the activist, the performative and the curatorial, the architectural and the urban. Acting upon and engaging with the public realm, the field of spatial practices allows people to reconnect with their own sense of agency through engagement in space and place, exploring and prototyping alternative futures in the here and now. The 24 chapters contain essays, visual essays and interviews, featuring contributions from an international set of experimental practitioners including Jeanne van Heeswijk (Netherlands), Teddy Cruz (Estudio Teddy Cruz + Fonna Forman, San Diego), Hector (USA), The Decorators (London) and OOZE (Netherlands). Beautifully designed with full colour illustrations, Spatial Practices advances dialogue and collaboration between academics and practitioners and is essential reading for students, researchers and professionals in architecture, urban planning and urban policy.
Introduction Melanie Dodd 1. Space is Always Political Melanie Dodd Part 1: Spatial Practices of Resistance; Protest, Occupation and Activism 2. Protest as a Spatial Practice Carl Fraser 3. Commons as Public: Re-inventing Public Spaces in the centre of Athens Ursula Dimitriou 4. Poor Relations: Community Activism as Spatial Practice Donna Turnbull 5. 'Popular Planning': A Conversation with Daisy Froud Melanie Dodd 6. A Long-Game of Resistance: Hugo Hinsley and Support Community Design Building Service Alex Warnock-Smith 7. 'Do-It-Yourself': A Conversation with Nicolas Henninger, EXYZT Shumi Bose 8. Reclaiming the City: Tactical spatial practices and the production of urban citizenship Oscar Brito Part 2: Spatial Practices of Intervention: Modes, Mediums, Objects, and Agency 9. The Making of the Canning Town Caravanserai Cany Ash, Ash Sakula 10. Of Soil and Water: King's Cross Pond Club Eva Pfannes and Sylvain Hartenberg, Ooze 11. 'Training for the Not-Yet' A Conversation with Jeanne van Heeswijk Melanie Dodd 12. 5 past 1 until 5 to 2 (on Thursdays) Anna Hart and Tilly Fowler, AIR 13. Glastonbury: Instant City Juliet Bidgood 14. 'As if a cloud had come down': A Conversation with Markus Bader, Raumlabor Berlin Andreas Lang 15. Spatial Narratives: A Critical Position Tricia Austin 16. Telling Stories: Interactions and Experiences on the Civic Stage David Chambers and Kevin Haley, Aberrant 17. 'Rehearsing Fictions': A Conversation with The Decorators Melanie Dodd and Shumi Bose Part 3: Spatial Practices within the City: Strategy, Disruption, and Critique 18. Disruptive Praxis: Critical Proximities at the Border: 10 notes on the Redistribution of Knowledges Across Walls Teddy Cruz and Fonna Forman 19. 'Fuzzy Edges': A Conversation with Liza Fior, muf Architecture/Art Melanie Dodd 20. 'Design for Organizing': A Conversation with Damon Rich and Jae Shin, Hector Design Melanie Dodd and Shumi Bose 21. Solidarity and Freedom: Educating for Spatial Practices Jeremy Till 22. Pedagogical Tools for Civic Practice Andreas Lang 23. 'New Municipalism': A Conversation with Finn Williams and Pooja Agrawal, Public Practice Melanie Dodd and Shumi Bose 24. Socializing Practice: From Small Firms to Cooperative Models of Organization Aaron Cayer, Peggy Deamer, Shawin Roudbari, Manuel Shvartzberg Carrió Index
OCLC-licensed vendor bibliographic record.
Keywords: Space (Architecture); Architecture and society; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting; ARCHITECTURE / Urban & Land Use Planning